2007
DOI: 10.1016/j.neuroscience.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Learned helplessness is independent of levels of brain-derived neurotrophic factor in the hippocampus

Abstract: Reduced levels of brain-derived neurotrophic factor (BDNF) in the hippocampus have been implicated in human affective disorders and behavioral stress responses. The current studies examined the role of BDNF in the behavioral consequences of inescapable stress, or learned helplessness. Inescapable stress decreased BDNF mRNA and protein in the hippocampus of sedentary rats. Rats allowed voluntary access to running wheels for either 3 or 6 weeks prior to exposure to stress were protected against stress-induced re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 100 publications
4
44
0
Order By: Relevance
“…This may not be the same for all paradigms as suggested by Greenwood et al, (2007) who showed that behavioral response was independent of hippocampal BDNF levels in their paradigm of learned helplessness where testing occurred in a novel environment. That study did however, show that wheel running protected against suppression of BDNF due to stress and suggested that this could counteract other behavioral consequences of reduced BDNF.…”
Section: Discussionmentioning
confidence: 82%
“…This may not be the same for all paradigms as suggested by Greenwood et al, (2007) who showed that behavioral response was independent of hippocampal BDNF levels in their paradigm of learned helplessness where testing occurred in a novel environment. That study did however, show that wheel running protected against suppression of BDNF due to stress and suggested that this could counteract other behavioral consequences of reduced BDNF.…”
Section: Discussionmentioning
confidence: 82%
“…Alternatively or additionally, the impairment of 5-HT 2A receptor signaling may result from mutual interaction between the 5-HT 2A receptor and brain-derived neurotrophic factor (BDNF). Inescapable stress could decrease the BDNF levels in the brain possibly due to high levels of brain glucocorticoids (Vaidya et al, 1997;Xu et al, 2006;Duman and Monteggia, 2006;Greenwood et al, 2007), whereas the function of the 5-HT 2A receptor appears to depend on BDNF as knockout of BDNF severely impairs 5-HT 2A receptor signaling (Rios et al, 2006). Thus, decrease of BDNF by inescapable stress may also participate in the occurrence of the impairment of 5-HT 2A receptor signaling.…”
Section: -Ht 2a Receptor-mediated Serotonergic Facilitation Of Gaba mentioning
confidence: 99%
“…The uncontrollable tail shock procedure followed protocols previously used in our laboratory that are known to produce exaggerated shock-elicited freezing and shuttle box escape deficits (Greenwood et al 2003(Greenwood et al , 2007b. Rats were randomly assigned to either be left in their home cages (No Stress) or to be exposed to the uncontrollable stress procedure (Stress).…”
Section: Uncontrollable Stressmentioning
confidence: 99%
“…Electrodes attached to the tail delivered 100 5-s tail shocks (1.5 mA) on a 1-min variable-interval schedule (Coulbourn Instruments, Allentown, PA, USA). This number and intensity of tail shocks were chosen based on prior work using this same stressor procedure (Greenwood et al 2003(Greenwood et al , 2007bMaier 1990) and a titration of the number of tail shocks required to produce escape deficits (Takase et al 2005). Following termination of shock, rats were returned to their home cages.…”
Section: Uncontrollable Stressmentioning
confidence: 99%
See 1 more Smart Citation